Probiotics and atopic eczema: a double-blind randomised controlled trial. (24th May 2012) - Allen, SJ; Jordan, S; Storey, M; Thornton, CA; Gravenor, MB; Garaiova, I; Jones, RH; Macfarlane, TV; Seager, AL; Manshian, B; Moller, M; Omakobia, M; et al.
Abstract : Aims: Atopic disorders are common in young children. The development of atopy may be influenced by exposure to microbes in early life. We tested the hypothesis that administration of a multi-strain probiotic during pregnancy and to young infants would prevent atopy in childhood. Methods: Pregnant women from 36 weeks gestation and their infants to age 6 months took daily either a probiotic consisting of two strains of lactobacilli and two strains of bifidobacteria or a matching placebo. Most infants had a first degree relative with atopy. The primary outcome was diagnosed eczema at age 2 years. Secondary outcomes were skin prick responses (SPRs) to common allergens and immune responses measured at birth and age 6 months. Results: 220 infants were randomised to the probiotic and 234 to the placebo group. A similar proportion of infants in the probiotic and placebo group developed eczema (34.1% and 32.4% respectively; p=0.71). A SPR to one or more common allergens occurred in 18/171 (10.5%) infants in the probiotic and 32/173 (18.5%) in the placebo group (OR 0.52, 95% CI 0.28-0.98). The main difference between the groups was in early sensitisation to cow's milk and hen's egg proteins. Atopic eczema (eczema and a positive SPR) occurred in 9/171 (5.3%) children in the probiotic and 21/173 (12.1%) in the placebo group (OR 0.40, 95% CI 0.18-0.91). Cord blood eosinophil count was reduced (p=0.024) and stimulated IL-12p70 concentrations in venous blood at age 6 months elevated (p = 0.022) in the probiotic compared with the control group. Conclusions: The probiotic reduced the frequency of atopic eczema and atopic sensitisation and promoted a Th1 orientation of the immune system. Probiotics administered during pregnancy and early infancy may be effective in the prevention of atopy.